Correlating elemental distribution with mechanical properties of TiN/SiNx nanocomposite coatings. (September 2019) - Sperr, M.; Zhang, Z.L.; Ivanov, Y.P.; Mayrhofer, P.H.; Bartosik, M.
Abstract: Detailed structural and chemical analyses reveal that Ti-Si-N coatings prepared with high nitrogen partial pressure and temperature are composed of nm-sized (nearly equiaxed) TiN crystallites encapsulated by ~1.0 nm thin Si-rich tissue phase. This nanocomposite structure allows for superior hardness (37.6 ± 1.5 GPa) and fracture toughness (4.5 ± 0.6 MPa√m). Contrary, deposition at lower nitrogen partial pressure and temperature does not allow for such a clear Si segregation during film growth, leading to nm-sized solid solution Ti1-x Six N crystallites. Although having the same Si content of 8.5 at.%, their hardness (32.1 ± 0.9 GPa) as well as fracture toughness (3.0 ± 0.2 MPa√m) is significantly lower. Graphical abstract: Unlabelled Image